Comparing UNDP Poverty Reduction Policies in Rwanda and Haiti: A Policy Transfer Perspective - Izzaturrahmah, Nur; Satriannisa, Hasna (Agile Governance and Innovation Measurement Journal, 2026)
This research aims to analyze the comparative implementation of UNDP poverty reduction policies in Rwanda and Haiti in the context of achieving the 2030 Sustainable Development Goals (SDGs), particularly Goal 1: No Poverty. Using a qualitative comparative method, this study explores the policy transfer process, adaptation, and outcomes in the two countries based on the Policy Transfer Theory by Dolowitz and Marsh. Data was collected from UNDP reports, country evaluations, and secondary sources. Rwanda was chosen as a case of relative success, while Haiti represents a case of limited effectiveness. The research found that Rwanda's success was driven by strong local adaptation, stakeholder participation, and integration of poverty policies with national development plans. In contrast, Haiti faces challenges such as weak governance, lack of local ownership, and over-reliance on external actors. The findings highlight that successful policy transfer requires contextual adaptation, institutional capacity, and inclusive governance. This research contributes to the understanding of global governance in development policy and emphasizes the importance of adapting international frameworks to local realities. It underscores how policy transfer mechanisms can support or hinder the achievement of global development goals depending on national conditions and the quality of governance.